Effect of Acupuncture Therapy Combination of Curcuma Xanthorrhiza Extract on Changes in Scale of Stomach Pain in Students of Campus 1 Polytechnic of the Ministry of Health Surakarta - Meutia Wahdini Nurhaiqa; Eka Deviany Widyawaty; Sumanto; Nurmila Mutiah (HAKTI : Indonesian Acupuncture Therapists Association, 2026)
Stomach pain or dyspepsia is a digestive disorder characterized by epigastric pain, a feeling of fullness, nausea, vomiting, and frequent belching. Although often considered mild, this condition poses a risk of serious complications such as peptic ulcers, perforation, and even stomach cancer, which can significantly impact the quality of life. This study aims to determine the effect of acupuncture therapy combined with turmeric extract on changes in the stomach pain scale among students at Campus 1 Poltekkes Kemenkes Surakarta. The study employed a